Friday

August 1, 2014

August 1, 2014

Posted by **Erik** on Wednesday, April 27, 2011 at 3:04pm.

Solve for x

lnx-lnx^2+ln5 = 0

Simplify the answer

- Math -
**MathMate**, Wednesday, April 27, 2011 at 3:16pmUse the law of logarithms:

ln(a)+ln(b)=ln(ab)

ln(a)-ln(b)=ln(a/b)

kln(a)= ln(a^{k})

ln(1)=0

ln(1/x)=-ln(x)

so

ln(x)-ln(x²)+ln(5)=0

ln(x/x²)+ln(5)=0

ln(1/x)+ln(5)=0

-ln(x)+ln(5)=0

ln(x)=ln(5)

e^(ln(x))=e^(ln(5))

x=5

**Related Questions**

L'Hopital's rule - Find lim x->1+ of [(1/(x-1))-(1/lnx)]. Here is my work...

calculus - sorry to ask a second question so soon, but i'm just not getting this...

math - how would you solve for y in this problem: ln(y-1)-ln2 = x +lnx ln(y-1)-...

math - I am suppose to simplify the following problems: sqrt(x)/x (isn't that ...

Math - Find the coordinates of the turning point and determine wether it is ...

Calculus 1 - Find the derivative of y with respect to x. y=(x^6/6)(lnx)-(x^6/36...

calc - integral of 1 to e^4 dx/x(1+lnx) 1+lnx = a => dx/x = da dx/ x(1+lnx...

Calculus - Find the derivatives, dy/dx for the following functions. a. x^2y^4 = ...

Logarithms - lnx^5 - lnx^2 = 3 solve for the unknowns as a list. I tried using ...

Math logs - Solve the system of equations: y= (lnx)^2 + 2 (lnx^2) y = 3ln(1/x^2...